Kajian tentang Penerapan Sanksi Pidana terhadap Pelaku yang Melakukan Perbuatan Curang dalam Bisnis Dihubungkan dengan Pasal 379a Kitab Undang-Undang Hukum Pidana - M Rendi Aridhayandi (Dialogia Iuridica, 2017)
Business is one of main activity in supporting national economic matter. Business activity run by businessman, varied according to their existence in regulation, activity or legal standing. In lower level for example, businessman are person with limited resources, but for middle or higher level, the activity run by business entity including incorporated and not a legal entity such person or cooperative as a corporation. This article examine legal aspect in applying criminal sanction to businessmen who act fraud in business according to Article 379a Criminal Code of Indonesia (KUHP). This article also examine the reason for those fraud action and analyze the enforcement by law enforcer. The result show that business is one of economic activity that seek profit but in some way the activity run by using inappropriate action which hurm other businessman. The reason for those fraud action are the weaknes of human resources; unethical behavior in business activity; and the weakness of law enforcement. Enforcement of article 379a in order to ensure legal certainty, equality before the law and legal protection still work slowly.